SIZE AND AGE AT FIRST MATURITY OF THE CRUCIFIX SEA CATFISH, Sciades proops (VALENCIENNES, 1840) (SILURIFORMES: ARIIDAE), CAUGHT OFF WESTERN MARANHÃO STATE, BRAZIL - Azevedo, James Werllen de Jesus; de Castro, Antonio Carlos Leal; Porto, Heliene Leite Ribeiro; Lima, Paulo Roberto Sousa (Arquivos de Ciências do Mar, 2010)
The aim of the present study was to determine size and age at first maturity of the crucifix sea catfish, Sciades proops, on the western coast of the state of Maranhão (Brazil) between the cities of São Luís (2° 32’S-44° 18’W) and Turiaçu (1°20’S- 45°20’W) from November, 2005 to August, 2006. One hundred sixty-one specimens were caught with gillnets operating at the surface, middle of the water column and bottom over a complete tide cycle. Mean size at first maturity for males and females was estimated as 35.2 cm and 36.6 cm, corresponding to 1.7 and 1.8 years, respectively. All males and females are able to reproduce at 41.7 cm and 44.7 cm, respectively. The results indicate larger variations in reproductive size for the species investigated when compared to data available in the literature.